Activating persuasion knowledge in native advertising: the influence of cognitive load and disclosure language. Issue 1 (2nd January 2020) - Jing Wen, Taylor; Kim, Eunice; Wu, Linwan; Dodoo, Naa Amponsah
Abstract: Incorporating the theory of limited cognitive capacity and persuasion knowledge model, this article examines the interaction effect between cognitive load and disclosure language on the activation of persuasion knowledge and perceived manipulativeness of native advertising. Two experimental studies suggested that individuals with varied levels of cognitive load responded to native advertisements using explicit versus implicit disclosure language differently. The current research contributes to theory building in the native advertising literature and provides practical implications to advertising practitioners and regulatory agencies.